Quality of life perceived by older adults attending the Integral Development of the Family (DIF) Huixquilucan, Mexico - López Fernández, Rosa (2020)
The aim of this research was to identify the perceived quality of life of the older adults attending elderly clubs in Huixquilucan, State of Mexico, and determine the sociodemographic factors related to that perception. The hypothesis was that older adults would have a high perception of their quality of life. A descriptive and correlational study, with a quantitative approach and a non-experimental cross-sectional design, was carried out. 479 older adults, chosen by a non-probabilistic and convenience sampling method, participated in the study. The RL Quality of Life scale was applied (López, 2016). The obtained data were analyzed using different statistical programs. The results showed a high perception of quality of life, reinforced by attending social activities; a significant relation between the following measured variables was observed: schooling, age, occupation, religion, marital status, who do they live with, having a caregiver and income level